The Intersection of AI Advancements in Judicial Systems and Media Trials - Ramadhani, Evyta (Faculty of Law, University of Jember, Indonesia, 2024)
In the ever-evolving landscape of jurisprudence, the integration of technology, particularly Artificial Intelligence (AI), has become increasingly prevalent, reshaping the dynamics of judicial proceedings and legal discourse worldwide. Concurrently, the phenomenon of